Ecotourism, Cultural Identity, and Social Transformation in Indigenous Island Communities: Evidence from Hukurila, Indonesia - Zetriani Uktolseja; Aholiab Watloly; Pieter Jacob Pelupessy; Fransina Matakena (Jurusan Sosiologi FISIP Universitas Pattimura, 2026)
This study examines the relationship between ecotourism development, cultural identity, and social transformation within the indigenous island community of Hukurila. The research investigates how ecotourism shapes cultural preservation, community participation, and socio-economic transformation in the context of sustainable tourism governance. Employing a qualitative descriptive approach grounded in tourism sociology, data were collected through in-depth interviews, participant observation, documentation, and field notes involving customary leaders, local government officials, tourism managers, residents, youth groups, tourism entrepreneurs, and visitors. The findings reveal that ecotourism has strengthened local economic opportunities while simultaneously transforming social relations, livelihood patterns, and community participation. Indigenous cultural identity remains preserved through customary rituals, local wisdom, and traditional governance systems integrated into tourism practices. However, tourism expansion also generates sociological challenges, including cultural commodification, unequal access to tourism benefits, environmental pressures, and shifts in traditional authority structures. The study introduces the concept of “Indigenous Island Ecotourism Sociology,” emphasizing the interconnected relationship between marine ecology, customary institutions, cultural identity, social participation, and sustainable tourism governance. This research contributes to tourism sociology and indigenous studies by demonstrating that ecotourism functions not only as an economic activity but also as a medium of cultural resilience, identity negotiation, and community adaptation in coastal societies.